NASA-TLX Mental Workload Analysis of Agrarian Reform Access Field Staff at Kantor Pertanahan X - Malahayati, Aisyah Juliawulan; Yulia Sawitri; Tachtassara Zulkarnain; Friesca Erwan (Journal of Advances in Information and Industrial Technology, 2026)
Agrarian Reform Access activities require field staff to integrate field and administrative responsibilities, including data collection, field verification, community coordination, data processing, mentoring, and report preparation. In public land administration, this integrated role requires a workload evaluation approach that can describe both the overall workload level and its dominant dimensions. This study applied the NASA Task Load Index (NASA-TLX) as a practical diagnostic method to assess the perceived mental workload of field staff at Kantor Pertanahan X and to formulate dimension-based improvement directions. A descriptive quantitative survey was conducted using a total sampling of all eight field staff members. The results showed an average NASA-TLX score of 89.88, indicating a high level of perceived mental workload; all respondents were classified in the high workload category, with scores ranging from 82.00 to 99.33. The dominant dimensions were Performance, Mental Demand, and Effort, suggesting that respondents perceived their workload most prominently in relation to program target achievement, cognitive processing of field and administrative data, and the effort required to complete interconnected tasks. These findings should be interpreted as descriptive perceived workload patterns rather than causal relationships. Compared with general workload evaluation approaches, NASA-TLX offers the advantage of identifying both aggregate workload and dimension-level profiles. The findings support targeted improvements in task distribution, work scheduling, reporting formats, technical support, and internal coordination in Agrarian Reform Access activities.